THE INFLUENCE OF THE FACTORS OF SEX, AGE, AND METHOD OF INOCULATION UPON THE COURSE OF EXPERIMENTAL SYPHILIS IN THE RABBIT - Chesney, Alan M. (The Rockefeller University Press, 1923)
For convenience the results are summarized in tabular form. Table I shows a comparison of the primary reaction in the groups of female and male rabbits inoculated intradermally. In Table II the incidence of metastatic lesions is shown in the various groups of animals. In Table III are shown the character and date of appearance of the generalized lesions (exclusive of orchitis) in the various groups of animals. The results presented in Tables I, II, and III, together with a study of the individual protocols, permit the following general statements to be made relative to the effect of the factors studied upon the course of experimental syphilis in the rabbit. Sex.—In the group of females inoculated intradermally the lesions at the site of inoculation were in general less marked than in the group of males similarly inoculated. Moreover, they attained their maximum size earlier and began to recede earlier than was the case in the males. In none of the females was there clinical evidence of the production of generalized lesions, while in the corresponding group of males metastatic lesions of skin or bones detectible by clinical examination occurred in one instance, or 14.3 per cent. In both groups there was wide variation in the character of the initial reaction in individual rabbits and in the time required for it to reach its maximum size. See PDF for Structure Age.—In the five young males inoculated intratesticularly the disease was not greatly different from that observed in the older males similarly inoculated. The initial reactions were slightly slower in making their appearance, but the magnitude of the reaction, as judged by enlargement of the testicles, was somewhat greater. The percentage incidence of metastatic orchitis was almost the same in the two groups. The younger animals showed a slightly greater incidence of generalized lesions involving structures other than the testicles, although the difference was insignificant, but the lesions were smaller, fewer in number, and confined entirely to the skin, and there was no instance of severe generalized lesions. Moreover, the occurrence of metastatic lesions (skin) in the younger animals was definitely delayed. Method of Injection.—In the animals inoculated by the intratesticular route the development of the primary reaction and the incidence of generalized lesions involving skin and bone were much greater than in See PDF for Structure the animals inoculated intradermally. Thus, of the latter group only one, or 14.3 per cent, showed a secondary metastatic lesion (skin), while in the group inoculated by the testicular route the incidence of metastatic skin and bone lesions was as high as 71.4 per cent. The difference in the character of the disease exhibited by these two groups of animals inoculated in a different manner is quite striking. Intratesticular inoculation produced a much more violent local reaction and a much greater incidence of generalized lesions than did intradermal inoculation. Effect of Castration.—In the group of animals with unilateral orchitis in which the infection was allowed to run its course without any attempt at suppression by removal of the initial focus, metastatic lesions appeared more promptly and in slightly greater incidence than See PDF for Structure in the group of animals in which the initial local reaction was suppressed by removal of the focus itself through castration. The percentage differences are not very great, but they are constantly in favor of the first group, as is the time interval of appearance. This experiment is not in strict accord with similar experiments observed by Brown and Pearce (3) in the past, and while the reasons for this difference are not clear the fact may be noted that the incidence of generalized lesions in uncastrated animals is somewhat higher than that reported by these authors, also that there was a high percentage of recurrence of primary lesions.